THE PROBLEM OF THE ORIGIN OF FELSIC ROCKS WITH A POSITIVE EU ANOMALY AS INDICATORS OF EXTENSION: EVIDENCE FROM THE EASTERN BALTIC SHIELD - Terekhov E.N. (My University, 2004)
A large amount of felsic rocks with positive Euanomaly have been studied in the high-grade metamorphic complexes of the eastern Baltic Shield. Most samples were taken from the Lapland-Belomorian Belt (LBB). However, similar rocks are known in other areas of the Baltic Shield, where they are attributed to the redistribution of REEs during granitization or magmatic crystallization. Most rocks exposed at the Earth's surface show a negative or no Eu anomaly. Therefore, the study of rocks with a positive Eu anomaly can provide insight into the behavior of Eu in the Earth's crust and the specifics of the structural settings of their formation.